PENGEMBANGAN KAPABILITAS KOLABORASI DINAMIS UNTUK MENINGKATKAN KINERJA BISNIS KOPERASI JASA KEUANGAN SYARIAH DI JAWA TENGAH - Faqih Nabhan (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
Since the last two decades, there has been controversy over the influence of collaborative partnerships on the performance of the organization. At the practical level, the low number of mudaraba and musharaka practices in the financing on Islamic financial institutions shows the significancy of conceptual frameworks in developing organizational capability in conducting collaborative partnerships that can improve the performance of Islamic financial institutions. Through in-depth theoretical and empirical study, it can be presented a conceptual model of the dynamic collaboration capabilities to enhance the business performance of Islamic financial institutions. The population was Islamic Financial Services Cooperatives in Central Java with 151 respondents spread over several districts and cities in Central Java. The study used purposive sampling and Structural Equation Model (SEM) to analyze the data.